Talent identification among elite Czech male junior tennis players (U12) according to their future tennis performance and birthdate - Polách, Michal; Jiří, Zháněl; Agricola, Adrián; Kellner, Petr; Vespalec, Tomáš (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Talent identification (TI) in sport, which is the selection of individuals disposed to achieve elite performance in adulthood, is often based on physical fitness testing. TI is linked to the phenomenon called the Relative Age Effect (RAE), referring to the influence of birthdate on sports performance. This retrospective study is based on the assumption that elite adult athletes possessed indicators predictive of a successful career already at a young age. The study aimed to assess the differences among Czech male tennis players according to 1) their tennis performance in adulthood, 2) their birthdate in each semester (S). The participants were players U12 who were later among top 1000 in the ATP Singles Rankings (SR). The research data was obtained during regular testing of the Czech Tennis Association (1998–2019). Significant differences between subgroups R1 (SR 1st - 500th) and R2 (SR 501st - 1000th) were found, surprisingly in favor of R2 in 4 variables. Significant differences were found in favor of B1 (born in S1) in 2 variables, and in favor of B2 (born in S2) in 2 variables.